Identifying the critical success factors in the implementation of Enterprise Resource Planning (ERP) in the Zimbabwe electricity energy sector - Chipanga, Fibian (Department of Construction Economics and Management, 2021)
The study identified CSFs and their prioritisation in ERP implementations in the Zimbabwean electricity energy sector context. This research paper discusses key recommendations for improving future Enterprise Resource Planning (ERP) implementations based on insights from an exploratory qualitative single case study in the Zimbabwean electricity sector. The design was an interpretive case study research with the data collected using face to face and telephonically interviews from eighteen participants belonging to four project role groups of project managers, module owners, supper (key) users and end users. The researcher conducted in depth interviews with four role groups. The following critical success factors were identified and discussed: Business Plan and Vision, Business Process Reengineering, Change Management, Communication, ERP System selection, ERP Team composition and competence, External Expertise, IT Infrastructure, Project Management, Top Management Support and Commitment, Training and Education, User Involvement and Vendor Support. The findings from this study can be used to contribute additional insight on the implementation of ERP systems in the electricity energy sector in the Zimbabwean context. This paper is significant because identification and prioritisation of critical success factors help organisations institute appropriate strategies to enhance the successful implementation of ERP system and increase the realisation of the benefits of ERP systems. Management must be able to use the rankings of the CSFs for resource allocation and improved human management.